Identification and reconstruction of phylogeny among three species of Cleome using nrDNA-ITS sequence - Khan, Salim; Al-Qurainy, Fahad; Nadeem, Mohammad; Tarroum, Mohamed; Alansi, Saleh; Gaafar, Abdel-Rhman; Alshameri, Aref; Shaikhaldein, Hassan O.; Salih, Abdalrhaman M.; Alenezi, Norah Arrak (International Journal of Applied and Experimental Biology, 2023)
Three species of genus Cleome, C. arabica, C. ramosissima and C. amblyocarpa were identified using nuclear ribosomal DNA internal transcribed spacer sequence (nrDNA-ITS). The phylogenetic tree was made using different methods viz., neighbor-joining (NJ), maximum parsimony (MP), and maximum likelihood for accuracy of the results, and congruence finding in phylogeny. Cleome ramosissima and C. amblyocarpa were found to be clustered in one group according to the sequence similarity. However, C. arabica clustered in a separate clade. The nrDNA-ITS marker clearly differentiated and showed phylogenetic relationships among the three species. Thus, nrDNA-ITS marker could be effectively used for other species of Cleome for their identification and phylogenetic studies.